Cosmopolitan cities: the frontier in the twenty-first century? - Sevincer, A. Timur; Kitayama, Shinobu; Varnum, Michael E. W. (Frontiers in Psychology, 2015)
People with independent (vs. interdependent) social orientation place greater priority on personal success, autonomy, and novel experiences over maintaining ties to their communities of origin. Accordingly, an independent orientation should be linked to a motivational proclivity to move to places that offer economic opportunities, freedom, and diversity. Such places are cities that can be called “cosmopolitan”. In support of this hypothesis, Study 1 found that independently oriented young adults showed a preference to move to cosmopolitan rather than noncosmopolitan cities. Study 2 used a priming manipulation and demonstrated a causal impact of independence on residential preferences for cosmopolitan cities. Study 3 established external validity by showing that students who actually moved to a cosmopolitan city were more independent than those who either moved to a noncosmopolitan city or never moved. Taken together, the findings illuminate the role of cosmopolitan settlement in the contemporary cultural change toward independence and have implications for urban development and economic growth.